2020
DOI: 10.3390/cryst10060457
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of the Incorporation of V2+, V3+, V4+, V5+ and Mo3+, Mo4+, Mo5+, Mo6+ Dopants in LiNbO3

Abstract: The doping of LiNbO3 with V2+, V3+, V4+ and V5+ as well as Mo3+, Mo4+, Mo5+ and Mo6+ ions is of interest in enhancing its photorefractive properties. In this paper, possible incorporation mechanisms for these ions in LiNbO3 are modelled, using a new set of interaction potentials fitted to the oxides VO, V2O3, VO2, V2O5 and to LiMoO2, Li2MoO3, LiMoO3, Li2MoO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There is no theoretical nor experimental data reported so far in the literature on the studied properties of this NiV x Sc 1−x Sb quaternary system We provide in table 1 the equilibrium structure parameters and the bulk moduli for these NiV x Sc 1−x Sb quaternary alloy that illustrates how these vanadium concentrations impact structural properties. Due to vanadium's small ionic radius of 0.640 Å as compared to the scandium's ionic radius of 0.745 Å, the lattice parameter in NiScSb decreases linearly with increasing vanadium concentration [41,43]. The following equation suggests that the weak discrepancies between the lattice parameters of compounds made of NiVSb and NiScSb ((a NiVSb − a NiScSb ) = −0.22, resulting in a linear decrease (with a slope of −0.22), that supports Vegard's law [44]:…”
Section: Nimentioning
confidence: 99%
“…There is no theoretical nor experimental data reported so far in the literature on the studied properties of this NiV x Sc 1−x Sb quaternary system We provide in table 1 the equilibrium structure parameters and the bulk moduli for these NiV x Sc 1−x Sb quaternary alloy that illustrates how these vanadium concentrations impact structural properties. Due to vanadium's small ionic radius of 0.640 Å as compared to the scandium's ionic radius of 0.745 Å, the lattice parameter in NiScSb decreases linearly with increasing vanadium concentration [41,43]. The following equation suggests that the weak discrepancies between the lattice parameters of compounds made of NiVSb and NiScSb ((a NiVSb − a NiScSb ) = −0.22, resulting in a linear decrease (with a slope of −0.22), that supports Vegard's law [44]:…”
Section: Nimentioning
confidence: 99%
“…) lithium on structural vacancy, v O oxygen vacancy. During recent years the existence of the following charge compensated complexes has been postulated most often: Nb Li + 4v Li [90,94,95] (including three-dimensional complexes 3v Li + Nb Li + v Li [96,97]), 5Nb Li + 4v Nb [98,99], 2Nb Li + 2Nb v + 3v Li + 3v Nb [96] and some others [100]. Some features accompanying the crystal growth (Li 2 O evaporation, variation of oxygen deficiency in Nb 2 O 5-x [101]) and specific changes of some crystal properties after thermal oxidation and/or reduction definitely indicate that the oxygen sub-lattice is not always perfect and stable as well; therefore the oxygen non-stoichiometry has been also discussed for a long time [102][103][104][105].…”
Section: Charge Compensation and Intrinsic Defectsmentioning
confidence: 99%
“…Vanadium and molybdenum ions are of interest in enhancing the photorefractive properties of LiNbO 3 . Paper [2] presents a computer modelling study of V 2+ , V 3+ , V 4+ and V 5+ as well as Mo 3+ , Mo 4+ , Mo 5+ and Mo 6+ in LiNbO 3 using interatomic potentials. It was found that divalent (V 2+ ), trivalent (V 3+ , Mo 3+ ) and tetravalent (V 4+ ) ions are incorporated at the Li and Nb sites through the self-compensation mechanism.…”
Section: Photorefractive Properties and Defect Structurementioning
confidence: 99%